Students Attendance System (SAS) - Ramli, Aimran; Abdul Latip, Mohd Hanapi; Mohamed, Hasiah; Mohd Adzmi, Nurul Husna Amalina (International Journal of Advanced Science Computing and Engineering, 2019)
In UiTM Terengganu, student attendance current manual processis based on Academic Affairs (HEA) criteria. Lecturer has tobring attendance sheet to each class and take student attendance.At the end of semester lecturer has to manually calculate andsend the report to HEA. Based on preliminary study, currentprocess causing inefficiency on processing reporting. In order toimprove the current process, Student Attendance System (SAS) isa system proposed to be developed for Universiti TeknologiMARA (UiTM) Terengganu. Lecturer is the primary users of thesystem. These allow user control, update, and view the attendancebased on session, course and group. SAS was developed withSystem Development Life Cycle based on Extreme Programming(XP). XP phases involve phase of select user stories for release,then break down stories to tasks, plan release, develop, release toevaluate it. Then, process is repeated until meet user requirement.System testing based on test plan has been conducted. As for theevaluation, the evaluation process is done by three (3) expertsthen comment and suggestion is produced. Results based onexperts evaluation shows that positive feedback from the expertswhere the development of SAS caters elements of ease of use,flow is easy to be understood and the system is consistent andfollow the standard As conclusion, SAS can be improved basedon comments and suggestions form experts and it has a bigpotential to be implemented in UiTM Terengganu.